Neutrophils Induced Licensing of Natural Killer Cells. (21st April 2015) - Amano, Keishiro; Hirayama, Masahiro; Azuma, Eiichi; Iwamoto, Shotaro; Keida, Yoshitaka; Komada, Yoshihiro
Abstract : Natural killer (NK) cells acquire effector function through a licensing process and exert anti-leukemia/tumor effect. However, there is no means to promote a licensing effect of allogeneic NK cells other than cytomegalovirus reactivation-induced licensing in allogeneic hematopoietic stem cell transplantation in human. In mice, a licensing process is mediated by Ly49 receptors which recognize self-major histocompatibility complex class I. The distribution of four Ly49 receptors showed similar pattern in congenic mice, B10, B10.BR, and B10.D2, which have B10 background. Forty Gy-irradiated 2 × 10 6 B10.D2 cells including splenocytes, peripheral blood mononuclear cells in untreated mice, or granulocyte colony-stimulating factor treated mice were injected intraperitoneally into B10 mice. We found that murine NK cells were effectively licensed by intraperitoneal injection of donor neutrophils with its corresponding NK receptor ligand in B10 mice as a recipient and B10.D2 as a donor. Mechanistic studies revealed that NK cells showed the upregulation of intracellular interferon- γ and CD107a expression as markers of NK cell activation. Moreover, enriched neutrophils enhanced licensing effect of NK cells; meanwhile, licensing effect was diminished by depletion of neutrophils. Collectively, injection of neutrophils induced NK cell licensing (activation) via NK receptor ligand interaction.